Hermens, E.; Fiske, T., eds. (2009). Art, Conservation and Suthenticities : Material, Concept, Context. London: Archetype Publications, 266 p. - Morales, María Ana (Universidad Nacional de San Martín. UNSAM Edita, 2014)
Artículo de anuario